Odpowiedź :
Odpowiedź:
I.
2.
4a + 15 = -5
3.
3x + 2 = 2(x + 1)
3x + 2 = 2x + 2
3x - 2x = 2 - 2
x = 0
4.
-5x + 10 = -2x - 8
-5x + 2x = -8 - 10
-3x = -18 /:(-3)
x = 6x
5.
7x + 14 = 5x - 22
7x - 5x = -22 - 14
2x = -36 /:2
x = -18
6.
2(x - 3) + 3(4 - x) = 5
2x - 6 + 12 - 3x = 5
-x = 5 - 6 /*(-1)
x = 1
7.
x + 2(3x - 4) = 53 + 2x
x + 6x - 8 = 53 + 2x
7x - 2x = 53 + 8
5x = 61 /:5
x = 12 1/5
8.
3x - 2 + 5x + 6 - x = 4x - 2 + 6x
7x - 10x = -2 - 4
-3x = -6 /:(-3)
x = 2
II.
a)
-5x + 10 = -2x - 8
-5x + 2x = -8 - 10
-3x = -18 /:(-3)
x = 6
b)
7x + 14 = 5x - 22
7x - 5x = -22 - 14
2x = -36 /:2
x = -18
c)
-3 + 2x - 6 = 3 - 4x
2x + 4x = 3 + 9
6x = 12 /:6
x = 2
d)
-5x + 12 + x = 2x - 12
-4x - 2x = -12 - 12
-6x = -24 /:(-6)
x = 4
e)
2(x - 3) + 3(4 - x) = 5
2x - 6 + 12 - 3x = 5
-x = 5 - 6 /*(-1)
x = 1
f)
2(x + 4) - 5(x + 3) = 2
2x + 8 - 5x - 15 = 2
-2x = 2 + 7 /:(-2)
x = -9/2 = -4 1/2
g)
3(x - 4) - 2(2x - 5) = -4
3x - 12 - 4x + 10 = -4
-x = -4 + 2 /*(-1)
x = 2
h)
-2(x + 3) + 4(2x + 3) = -6
-2x - 6 + 8x + 12 = -6
6x = -6 - 6 /:6
x = -12/6 = -2
Szczegółowe wyjaśnienie: